Meta-analysis of structural and functional brain alterations in internet gaming disorder - Niu, Xiaoyu; Gao, Xinyu; Zhang, Mengzhe; Yang, Zhengui; Yu, Miaomiao; Wang, Weijian; Wei, Yarui; Cheng, Jingliang; Han, Shaoqiang; Zhang, Yong (Frontiers in Psychiatry, 2022)
Background: Many neuroimaging studies of internet gaming disorder (IGD）have reported structural and functional abnormalities in brain regions. However, the findings were divergent. Our aim was to quantitatively integrate these studies by conducting a meta-analysis of gray matter volume (GMV) and functional neural activation, respectively, with a view to identifying consistent neural changes in IGD. Method: A systematic search was conducted in several databases from Jan 1, 2010, to Oct 31, 2021, to identify eligible voxel-based morphometry (VBM) and functional magnetic resonance imaging (fMRI) studies. Brain alternations between IGD subjects and healthy controls (HCs) were compared using the anisotropic seed-based d mapping (AES-SDM) meta-analytic method. Meta-regression analysis was used to investigate the relationship between GMV alterations and addiction-related clinical features. Results: The meta-analysis contained 15 VBM studies (422 IGD patients and 354 HCs) and 30 task-state fMRI studies (617 IGD patients and 550 HCs). Compared with HCs, IGD subjects showed: (1) reduced GMV in the bilateral anterior/median cingulate cortex, superior/inferior frontal gyrus and supplementary motor area; (2) hyperactivation in the bilateral inferior frontal gyrus, precentral gyrus, left precuneus, right inferior temporal gyrus and right fusiform gyrus; (3) hypoactivation in the bilateral lingual gyrus and the left middle frontal gyrus; and (4) both decreased GMV and increased activation in the left anterior cingulate. Furthermore, Meta-regression revealed that GMV reduction in left anterior cingulate were positively correlated with BIS-11 score (r=0.725, p=0.012(uncorrected)) and IAT score (r=0.761, p=0.017(uncorrected)). Conclusions: This meta-analysis showed that IGD subjects had significant brain GMV and neural activation alterations compared with HCs. Furthermore, multi-domain assessments captured different aspects of neuronal changes in IGD, which may help develop effective interventions as potential therapeutic targets.